The relationship between classroom support and mathematical resilience - Hamidy, Anwaril; Vollstedt, Maike; Duchhardt, Christoph (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Mathematical resilience is a construct that plays a role in mitigating the prevalence of mathematics anxiety and other negative attitudes towards mathematics. In addition, it is interrelated to social factors such as support. Thus, this study examines the relationship between the three facets of mathematical resilience (Value, Struggle, and Growth) and classroom support (mathematics teacher support and classmates support). In total, 863 (60.8 % female, 2.9% did not answer) Indonesian 9th and 10th-graders answered 5-point Likert scales of mathematics teacher support, classmates support, and mathematical resilience. Structural Equation Modeling with Maximum Likelihood with robust standard errors was used for the main data analysis. The results revealed that mathematics teacher support was positively related to students’ Value and Struggle, but not to Growth. While classmates support was positively significant to students’ Value, it was not related to Struggle. Surprisingly, classmates support had a negative relationship with students’ Growth. The results offer a better understanding of the role of mathematics teachers in fostering and presenting suitable challenges to cultivate students’ mathematical resilience. Moreover, it is advisable for schools to thoughtfully approach the grouping of students to avoid the development of a fixed mindset that could arise among peers.